St. Kitts and Nevis : Ex Post Evaluation of Exceptional Access Under the 2011 Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for St. Kitts and Nevis. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses St. Kitts and Nevis' Ex Post Evaluation of Exceptional Access Under the 2011 Stand-by Arrangement. The program focused on (1) an ambitious fiscal consolidation, (2) a comprehensive debt restructuring, and (3) a further strengthening of the financial sector. These goals aimed to address the key issues behind the debt crisis, and the potential financial sector outcomes of the restructuring. The program had many successes. The debt reduction was one of the largest in recent times, the headline fiscal and current account balances improved substantially, important tax and public financial management reforms were enacted, and sovereign risk was removed from the banks. Robust growth also resumed.